EDUKASI PENCEGAHAN TERJADINYA CEDERA ANKLE SPRAIN DI KOMUNITAS LINE DANCE - Mualifah, Alif Andini; Atika Yulianti; Okti Umi Widhayati (Rena Cipta Mandiri, 2025)
Ankle sprain injury is a musculoskeletal injury that often occurs due to excessive ankle activity during activities. Most of these injuries are mild and can be overcome with self treatment. Therefore, it is necessary to provide outreach and education regarding proper and correct management of ankle sprain injuries. This outreach activity aims to increase the understanding of Line Dance community members regarding proper and correct treatment if they experience an ankle sprain injury. The method of this activity is observation, interviews, delivering material using posters, giving questionnaires to respondents who are members of the Line Dance community. The results of this activity received a very good response from members of the Line Dance community, with the provision of educational outreach on the prevention of ankle sprains which can increase better understanding.